Development of a method for forming a positive image of companies in the labor market of Ukraine - Hatylo, Valentyna (Technology audit and production reserves, 2019)
The object of research is the process of forming the image policy of enterprises in the labor market of Ukraine. One of the most problematic places of research is the theoretical justification and development of organizational and methodological recommendations on the process of forming the image policy of an enterprise in the labor market to attract potential employees. A review of publications devoted to the peculiarities of forming the image policy of enterprises in Ukraine shows that in order to successfully solve the problem of purposefully forming a positive image of an enterprise on the Ukrainian labor market, it is necessary: – a thorough analysis of the external and internal conditions of the enterprise’s activity; – development of image formation goals and justification of ways and means to achieve them. A methodological approach to the formation of a positive image of the enterprise on the labor market in the form of a sequence of stages and a set of methods is proposed. The difference from the well-known schemes of the image policy formation process is the reflection in the formation of the image policy of the constancy and continuity of this process. Long-term provision of the organization with human resources is one of the promising tasks for a modern enterprise, especially with a shortage of highly qualified personnel in the labor market. The principles of forming the internal image are highlighted: the principle of congruency, the principle of unity of command and standardization, the principle of compliance. To simulate the process of forming a positive image, a model for forming the image of an enterprise in the labor market is proposed. The basic elements of forming the image policy of the enterprise on the labor market for the various stages of cooperation with the corporation are given. It is proposed to evaluate the effectiveness of image formation in the labor market in four areas: analytical, production, information and management. Further research is planned to be carried out as part of the assessment of the effectiveness of the use of visual and verbal means of forming the image of the enterprise, which can be reflected in the form of a passport of the image of the enterprise. The passport should be based on an assessment of the presence in the personnel policy of a particular enterprise of the basic components that form a positive or negative image of the enterprise in the labor market.